A facilitated process and online toolset to analyze complex systems and coordinate active watershed development and transformation - Herzog, Margaret T., author; Labadie, John W., advisor; Grigg, Neil S., advisor; Sharvelle, Sybil, committee member; Lacy, Michael G., committee member; Clayshulte, Russell N., committee member (Colorado State University. Libraries, 2014)
Integrated Water Resources Management (IWRM) coordinates public, private, and nonprofit sectors in strategic resource development, while emphasizing holistic environmental protection. Without more integrated efforts, adverse human affects to water, other natural resources, and ecosystems services may worsen and cause more unintended cross-scale effects. Meanwhile, fragmented jurisdictional controls and competing demands continue to create new obstacles to shared solutions. Lack of coordination may accentuate negative impacts of extreme events, over-extraction, and other, often unrecognized threats to social-ecological systems integrity. To contend with these challenges, a research-based, facilitated process was used to design an online toolset to analyze complex systems more holistically, while exploring more ways to coordinate joint efforts. Although the focus of the research was the watershed scale, different scales of social-ecological problems may be amenable to this approach. The process builds on an adaptive co-management (ACM) framework. ACM promotes systems-wide, incremental improvements through cooperative action and reflection about complex issues affecting social-ecological systems at nested and overlapping scales. The resulting ACM Decision Support System (DSS) process may help reduce fragmentation in both habitat and social structure by recognizing and encouraging complex systems reintegration and reorganization to improve outcomes. The ACM DSS process incorporates resilience practice techniques to anticipate risks by monitoring drivers and thresholds and to build coordinated coping strategies. The Bear Creek Watershed Association (BCWA) served as a case study in nutrient management, which focused on understanding and mitigating the complex causes of cultural eutrophication in Bear Creek Reservoir - a flood control reservoir to which the entire watershed drains. The watershed lies in the Upper South Platte River Basin -the eastern mountain headwaters to metropolitan Denver, Colorado in the United States. To initiate Phase I of the ACM DSS process, qualitative data on issues, options, social ties, and current practices were triangulated through organizational interviews, document review, a systems design group, and ongoing BCWA, community, river basin, and state-level participation. The mixed methods approach employed geographic information systems (GIS) for spatial analysis, along with statistical analysis and modeling techniques to assess reported issues and potential options quantitatively. Social network analysis (SNA) was used systematically to evaluate organizational relationships, transactions, and to direct network expansion towards a more robust core-periphery network structure. Technical and local knowledge developed through these methods were complimented by ongoing academic literature review and analysis of related watershed efforts near and far. Concurrently, BCWA member organizations helped to incrementally design and test an online toolset for greater emphasis on ACM principles in watershed program management. To date, online components of the ACM DSS include issues reporting, interactive maps, monitoring data access, group search, a topical knowledge base, projects and options tracking, and watershed and lake management plan input. Online toolset development complimented assessment by formalizing what was learned together throughout the ACM DSS process to direct subsequent actions to align with this approach. Since the online system was designed using open source software and a flexible content management system, results can be readily adapted to serve a wider variety of purposes by adjusting the underlying datasets. The research produced several potentially useful results. A post-project survey averaged 9.3 on a 10-point satisfaction scale. The BCWA board adopted the resulting ACM DSS process as a permanent best management practice, funding a facilitator to continue its expansion. A network weaver to continually foster cooperation, a knowledge curator to expand shared knowledge resources, and a systems engineer to reduce uncertainty and ambiguity and dissect complexity were all found to be critical new roles for successful ACM implementation. Watershed program comparisons also revealed ten qualities that may promote ACM. The technical analysis of nutrient issues revealed that phosphorus enrichment from phosphorus desorption from fine sediments contributed to cultural eutrophication through several distinct mechanisms, which may be addressed through a wider range of non-point source controls and in-lake management options. Potential affects from floods, wildfires, and droughts were assessed, which has resulted in more coordinated, proactive plans and studies. Next steps include formulating multi-institutional, multi-level academic studies in the watershed, expanding community engagement efforts, and establishing innovation clusters. Multi-disciplinary research needs include studying nutrient exchange processes, piloting decentralized wastewater treatment systems, optimizing phosphorus removal processes, chemically blueprinting nutrient source streams, and developing an integrated modeling framework. At least four additional stages of development are planned to refine and mature the ACM DSS process over time. The ACM DSS process is also being considered for other places and IWRM problem sets.
Keywords: adaptive management; cultural eutrophication; decision support system; integrated water resources management; resilience practice; social network analysis